A Simulator for SMT Architectures: Evaluating Instruction Cache Topologies - Gonçalves, Ronaldo; Ayguadé, Eduard; Valero, Mateo; Navaux, Philippe (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41226, 2000)
SMT (Simultaneous MultiThreaded) is becoming one of the major trends in the design of future generations of microarchitectures. Its ability to exploit both intra- and inter-thread parallelism makes it possible to exploit the potential ILP (Instruction-level parallelism) that will be offered by future processor designs. SMT architectures can hide high latencies of instructions taking better advantage of the hardware resources through the simultaneous execution of a lot of diversified instructions from different threads. In order to provide detailed and accurate information about the performance of this approach, a SMT simulator has been developed on top of the SimpleScalar Tool Set. The SMT simulator allows the configuration of a large set of architectural parameters (cache and reservation station topologies, number of slots and branch prediction accuracy) in addition to the parameters originally inherited from the basic simulator (size of the cache memories, tables and queues, instruction scheduling policy and pipeline width). The SMT simulator has been exhaustively tested with workloads composed of some SPEC95 benchmarks and under different instruction cache topologies. The simulator has proved to be an efficient tool for the performance evaluation of these kind of architectures. The paper describes the main features of this simulator and analyses the simulation results.